Heat generation effect on mixed convection flow of viscoelastic nanofluid: convective boundary condition solution - Rahimah, Mahat; Noraihan Afiqah, Rawi; Abdul Rahman, Mohd Kasim; Sharidan, Shafie (Penerbit UTM Press, 2020)
The steady two-dimensional mixed convection boundary layer flow of viscoelastic nanofluid past a circular cylinder by considering convective boundary condition with heat generation has been studied numerically. For the case of nanofluid, the base fluid chosen is Carboxymethyl cellulose solution (CMC) and the nanoparticle is copper. The Tiwari-Das model has been considered in this study. Similarity transformation has been introduced by reducing the governing partial differential equations to a system of ordinary differential equations. Then, the Keller-box is applied to solve the nonlinear similarity. The numerical results are presented graphically and analytically for different values of the parameters including the heat generation parameter, nanoparticles volume fraction, and Biot number. A systematic study is discussed to analyze the effect of these parameters on the velocity and temperature profiles, as well as the skin friction and heat transfer coefficient. The thermal boundary layer shows the changes in variation behavior when the nanoparticles volume fraction, heat generation, and Biot number are increased. Heat transfer coefficient is an increasing function of heat generation parameter. Nanoparticles volume fraction on heat transfer coefficient has the opposite effect when compared with the heat generation parameter.